Analisis Kritis Penerapan Tanggung Jawab Hukum Lingkungan dalam Penanggulangan Eksploitasi Sumber Daya Alam - Marifah Marifah; Nanang Hermansyah; Arida Mahmudyah; Rudy Habibie (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
The massive exploitation of natural resources in Indonesia poses serious problems for environmental sustainability, thereby requiring the strengthening of environmental legal responsibility as an instrument of ecological control and protection. This study aims to analyze the legal framework, implementation, and effectiveness of environmental legal responsibility in the management and control of natural resource exploitation. The research method used is normative legal research with a legislative, conceptual, and analytical approach, supported by secondary data in the form of legislation, legal doctrine, and research results and official reports from state institutions. The results and discussion show that although environmental law principles such as state responsibility, the polluter pays principle, and sustainable development have been accommodated in various regulations, their implementation still faces obstacles in the form of weak law enforcement, sectoral policy fragmentation, and low compliance among business actors. These conditions have led to increased environmental degradation and conflicts over the use of natural resources. The conclusion of the study emphasizes that strengthening environmental legal responsibility requires regulatory harmonization, consistent law enforcement..